Evaluation of natural and synthetic photosensitizers in visible light-mediated antimicrobial photodynamic therapy against pathogenic bacteria - Seemi Tasnim Alam; Ferdousi Akhter; Esrat Jahan Toma; Most Farhana Khatun; Sadika Tasnim; Abdullah Bin Hossain Rayhan; Sadi Mahmud Sakib; Mehjabin Ferdous; Md. Aftab Uddin (American Journal of Biopharmacy and Pharmaceutical Sciences, 2026)
Objectives: Alternative effective treatment solutions to antibiotic resistance are long overdue. Antibiotic overuse and unfinished antibiotic courses have become globally life threatening, especially in Bangladesh. An alternative way to inactivate pathogenic microorganisms is antimicrobial photodynamic treatment (APDT). This study aims to explore the antimicrobial photodynamic activity of hypericin (a naturally occurring non-toxic photosensitizer [PS]) and methylene blue (a chemical PS), which in combination with light can generate reactive oxygen species, thus effectively destroying the bacterial cells. Materials and Methods: Clinically pathogenic bacteria, Staphylococcus aureus American Type Culture Collection (ATCC) 25923 and Escherichia coli ATCC 25922, were obtained from a diagnostic laboratory in Dhaka, Bangladesh. Antibiotic susceptibility profiling was performed using the Kirby–Bauer disk diffusion method on Mueller–Hinton Agar. Overnight bacterial cultures were incubated with the PS, followed by light exposure using an orange light-emitting diode light for 15 min. Post-treatment bacterial viability is assessed by enumeration of colony-forming units. Results: After APDT, successful reduction of S. aureus is seen up to log 3, and for E. coli , it was found log 1.5 reduction which was not significant. Antibiogram profiling showed 19 commercial antibiotic discs and found that S. aureus was resistant to doxycycline, gentamicin, and chloramphenicol while E. coli was resistant to ciprofloxacin, nalidixic acid, and cefixime. Conclusion: Gram-positive bacteria are more susceptible to APDT, as opposed to Gram-negative bacteria. The treatment has shown significantly successful results inactivating Gram-positive bacteria, but not remarkable for Gram-negative bacteria.